IDENTIFICATION DIGITAL TOURIST PREFERENCES USING SENTIMENT ANALYSIS: DEALING IN POST-PANDEMIC COVID-19 - Lutfia Septiningrum (Natapraja, 2022)
This aims to determine the post-pandemic impact on tourism in Rembang based on the results of community study using social media review. To achieve this goal, this study conducted a sentiment analysis of public comments/reviews regarding travel preferences after the COVID-19 pandemic using the support vector machine (SVM) classification method for digital tourism. Digital tourism is one of the innovations used to maintain the existence of tourism during the COVID-19 pandemic. At present the Covid-19 cases are starting to tilt, the number of tourist visitors has increased because the Indonesian government has begun to relax policies regarding the prevention of COVID-19. This also happened in Rembang Regency. Based on the Minister of Tourism and Creative Economy Regulation Number 9 of 2021 concerning Guidelines for Sustainable Tourism Destinations, digital tourism will boost the regional economy. To measure people's views, the sentiment analysis method is used to see people's preferences. The results accuracy value of 83% and an AUC value of 82.3% show the level of confidence on community reviews/comments using several digital platforms such as Twitter, YouTube, and the Rembang local government website in the good category. The classification of community preferences is stated in 2 groups, the first is the people says post-pandemic digital tourism must be developed, and the second states that they have decided to come directly to tourist attractions after Covid-19 in Rembang regency. Research suggestions for local governments to continue to develop digital tourism and continue to improve real tourism facilities and infrastructure in Rembang regencyt, where the pathway will increase tourist visits and the economy of the community around tourist attractions.